2018
DOI: 10.1002/jcp.27880
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic effects of curcumin: What is the evidence?

Abstract: Curcumin (diferuloylmethane), a component of the yellow powder prepared from the roots of Curcuma longa or Zingiberaceae (known as turmeric) is not only widely used to color and flavor food but also used as a pharmaceutical agent. Curcumin demonstrates anti‐inflammatory, anticarcinogenic, antiaging, and antioxidant activity, as well as efficacy in wound healing. Notably, curcumin is a hormetic agent (hormetin), as it is stimulatory at low doses and inhibitory at high doses. Hormesis by curcumin could be also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 101 publications
(183 reference statements)
3
40
0
3
Order By: Relevance
“…The antioxidant activity observed in cells can even decrease with increasing concentration [ 23 ], leading to curves that are not dose dependent. This behavior has been also reported in natural compounds such as curcumin or resveratrol, which present antioxidant effects at low doses but induce oxidative stress and cell death at high concentrations [ 166 , 167 ]. In this way, in vitro studies indicate that manganosalen complexes could also interact with other cellular pathways at high concentrations or with a receptor that could be suffering a threshold effect, that is, it would present higher affinity at low concentrations and would be desensitized at higher doses [ 168 ].…”
Section: Discussionmentioning
confidence: 55%
“…The antioxidant activity observed in cells can even decrease with increasing concentration [ 23 ], leading to curves that are not dose dependent. This behavior has been also reported in natural compounds such as curcumin or resveratrol, which present antioxidant effects at low doses but induce oxidative stress and cell death at high concentrations [ 166 , 167 ]. In this way, in vitro studies indicate that manganosalen complexes could also interact with other cellular pathways at high concentrations or with a receptor that could be suffering a threshold effect, that is, it would present higher affinity at low concentrations and would be desensitized at higher doses [ 168 ].…”
Section: Discussionmentioning
confidence: 55%
“…However, many reports provide evidence that low doses/concentrations of these compounds have the potential for adverse effects, such as enhancement of the proliferation of tumor cells [1,2]. Various phytochemicals demonstrate nonmonotonic dose/concentration-response termed biphasic dose-response and are considered to be hormetic compounds, for example, resveratrol [2,3] curcumin [4], sulforaphane [1]. The term hormesis described the phenomenon in which a chemical is able to induce biologically opposite effects at different doses; as dose decreases, there are not only quantitative changes in measured responses but also qualitative changes with reference to control and high dose level [5].…”
Section: Introductionmentioning
confidence: 99%
“…We have excluded curcumin from this work since its hormetic properties were recently reviewed elsewhere [4]. As data on the biphasic concentration/dose-response displayed by resveratrol were extensively reviewed in 2010 [2,3], we presented here reports concerning this subject published from 2010 until 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a chemical component extracted from the rhizome of Zingiberaceae and Araceae. Studies have described various effects of curcumin including reducing blood fat, choleretic actions, and antitumor, anti-inflammatory, and anti-oxidation effects [13][14][15][16] . Several studies have indicated that the effect of curcumin on SREBPs is related to the mechanism of curcumin regulating blood lipid metabolism [4,5,[8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%